Reducing “Golongan Putih” Activities in General Elections Abstention by Strengthening Citizen Participation and Involvement in Public Management - Muhamad Yusuf; Denok Kurniasih (Journal of Governance, 2023)
This article discusses efforts to reduce golongan putih or golput activities (abstention) in general elections by strengthening citizen participation and involvement in public management. Through political education, increasing access to information, encouraging active involvement, and increasing citizen capacity, it is hoped that voter participation can be increased. Strengthening citizen participation and involvement in public decision-making processes will strengthen democracy, increase government legitimacy, and ensure policies that better represent the public interest. This literature study involved 60 reputable national and international journals and international journals that had the keywords abstentions, elections, participation, involvement, and public management. The synthesis of community participation and abstention activities in public management includes several things, namely public participation and engagement, decision-making and the formation of public policy, abstentions and the fulfillment of voting rights, and a democratic environment. It can be concluded that public management as a reference for ideal community participation and involvement in general elections has a slice of direct study by creating open channels of communication, promoting inclusive political participation, building trust, and developing community involvement in public participation mechanisms.